Why go to France or Germany, if you could as well go to the UK or the US?: selective features of immigration to four major OECD countries - Wido Geis; Silke Uebelmesser; Martin Werding (Center for Economic Studies and ifo Institute (CESifo), 2008)
Building on a new data set which is combined from national micro-data bases, we highlight differences in the structure of migrants to four countries, viz. France, Germany, the UK and the US, which receive a substantial share of all immigrants to the OECD world. Looking at immigrants by source countries, we illustrate the important role of distance, both geographical and cultural, immigration policies and migrant networks. Differentiating immigrants by their educational attainments, we observe interesting patterns in the skill composition, employment opportunities and wages for migrants to the different destination countries. Focusing on migration between the four countries in our data set, we find that migration within Western Europe is small and rather balanced in terms of skill structures, while there appears to be a brain drain from Europe to the US.
Keywords: J21; J31; J61; O15; 330; Migration; immigration policy; education; employment; wages; brain drain; Migranten; Einwanderung; Bildungsniveau; Qualifikation; Brain Drain; Vergleich; Deutschland; Frankreich; USA; Großbritannien